Itsbat Nikah Terhadap Pernikahan Dibawah Umur Perspektif Mashlahah Mursalah (Studi Analisis Penetapan Nomor 4/Pdt.P/2022/PA.PP) - Ranti Rafika Dewi; Pendi Hasibuan; Arsal Arsal; Edi Rosman (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
The author's reason for raising this issue into a scientific work in the form of a thesis is because there are differences of opinion among judges at the Padang Panjang Religious Court regarding the itsbat of marriage for underage marriages in determining number 4/Pdt.P/2022/PA.PP which is the woman's party. when he got married he was 16 years old. First, the marriage certificate must be rejected because it has violated the law on marriage registration and the minimum age for marriage is 19 years. Second, the itsbat of marriage can be accepted on the grounds that it is mashlahah murslahah. How does the mashlahah mursalah analysis of this determination be explored by the author in this study. The author gives limitations on the problem regarding the legal considerations of the Panel of Judges regarding Determination Number 4/Pdt.P/2022/PA.PP and the analysis of mashlahah mursalah in determining number 4/Pdt.P/2022/PA.PP regarding itsbat marriage for underage marriages. This research is an analytical descriptive research by conducting an analysis of the determination of judges in the case of itsbat marriage for underage marriages, the research uses a normative juridical research type. This is because this legal research aims to examine legal principles, using qualitative data, namely data presented in the form of verbal words, not in the form of numbers. Primary data sources were obtained from Decree Number 4/Pdt.P/2022/PA.PP, Law Number 1 of 1974 concerning marriage and the Compilation of Islamic Law. In collecting data, it is done by taking inventory of data, classifying data, and then analyzing it by conducting a study of cases related to the issues faced in the determination of number 4/Pdt.P/2022/PA.PP and the laws and regulations using maslahah mursalah to then draw conclusions from the results of the analysis. From the results of the research that the authors conducted, it was found that: First, the basis for the legal considerations of the Panel of Judges in granting the application for itsbat marriage for underage marriages contained in the stipulation Number 4/Pdt.P/2022/PA.PP is Article 8 Law Number 1 of 1974 concerning the prohibition of marriage between two people who are related by blood, are related to semenda and are related to breastfeeding. Article 14 KHI regarding the pillars of marriage, namely the existence of a prospective husband, prospective wife, marriage guardian, two witnesses and consent and qabul. And for the benefit of the parties and the child, this is also in accordance with the rules of fiqh which reads "rejecting adversity must take precedence over taking benefit". Second, the legal considerations of the panel of judges in determining Number 4/Pdt.P/2022/PA.PP found mashlahah mursalah because by granting the itsbat of marriage for underage marriages, the couple can register their marriage at the Office of Religious Affairs because marriage registration aims to realize The purpose of law is for society to create order, certainty and legal protection, so that the civil rights of husbands, wives and children can be fulfilled.